Work-to-family effects of inclusive leadership: The roles of work-to-family positive spillover and complementary values - Zhu, Hong; Chen, Amy Y. Y. (Frontiers in Psychology, 2022)
Drawing on work–family enrichment theory, we explore whether inclusive leadership leads to employees’ work-to-family positive spillover, which further improves their family performance. We also focus on the moderating role of complementary values. A time-lagged study was conducted and the sample included 292 employees from two hotels. The results indicate that inclusive leadership triggers employees’ work-to-family positive spillover, and then their family performance is enhanced. Moreover, employees’ complementary values may strengthen the positive effect of inclusive leadership. We also provide theoretical and practical implications of the results.